في المؤسسات الكبيرة و دراسة تأثيره على أداء الشبكة IPv6 تطوير إطار عمل للانتقال إلى - التويتي، ماجد عبدالله; الشدادي، محمد محسن (University of Science and Technology, Yemen, 2015)
Because of the improvement in the information technology field, the technical revolution in communications sector and the huge increasing of the number of different devices that need IP addresses to connect to the Internet, the fourth version of Internet protocol (IPv4) is not able anymore to meet all the needs that the Internet users all around the world ask for. So that, moving toward the IP sixth version (IPv6) has become a very urgent necessity especially in the Yemen Republic which is already suffering from the lack of IPv4 addresses. This paper first studies the Internet Protocol IPv6 and its features and advantages and discusses in details the transition methods into IPv6. Then, the paper develops a framework with detailed plans for the big companies and organizations to achieve a seamless, successful, and smooth movement from IPv4 into IPv6. The developed framework with its associated plans has been applied to the University of Science and Technology-Yemen as a case study. After that, a detailed simulation based study is used to compare the effects of IPv4 and IPv6 application on the network performance and on the network response time when different type of services (such as Internet browsing, E-mail, files transfer, voice and video calls) are used. The study illustrates that the IPv6 has positive effects on the network performance and it also improves the network response time when different applications are used.